Evaluation of potential probiotic properties of Enterococcus mundtii, its survival in boza and in situ bacteriocin production - Todorov, Svetoslav Dimitrov (Array, 2009)
Summary: Boza is a low-pH and low-alcohol cereal-based beverage produced in the Balkan Peninsula. Barley was cooked and prepared according to a traditional recipe and inoculated with Enterococcus mundtii ST4V (a potential probiotic and bacteriocin-producing strain), commercially produced boza, Saccharomyces cerevisiae, and a combination of strain E. mundtii ST4V and Saccharomyces cerevisiae. Fermentation was carried out at 37 °C for 3 h. The organoleptic properties of fermented products were evaluated by a qualified taste panel. No significant differences in rheological properties were observed, suggesting that E. mundtii ST4V had no effect on the quality of the final product. Microbial cell numbers remained relatively unchanged during one week of storage. The preservative properties of bacteriocin ST4V were evaluated by contaminating boza with Lactobacillus sakei DSM 20017. Changes in microbial populations were monitored by using classical microbiological methods, PCR with species-specific primers and denaturing gradient gel electrophoresis (DGGE). Adsorption of bacteriocin ST4V to target cells is pH-dependent, with the highest adsorption (88 %) recorded at pH=8.0 and pH=10.0. Maximum adsorption of bacteriocin ST4V (75 %) to Enterococcus faecalis and Listeria innocua was recorded at 25 to 37 °C. Growth of E. mundtii ST4V was inhibited only by a few antibiotics and anti-inflammatory medicaments, suggesting that the strain may be used as a probiotic by individuals receiving medical treatment